Induction of somatic embryogenesis and cryopreservation of Abies pinsapo Boiss. - Cabero-Moreno, Laura; Landeras-López, Ignacio; Bravo-Navas, María Victoria; Sánchez-Romero, Carolina (Frontiers in Plant Science, 2025)
Abies pinsapo is an endangered species, endemic to southern Spain. Somatic embryogenesis and cryopreservation constitute important biotechnological tools, which can be used in order to improve the management and conservation of threatened species. The objective of this work was to develop somatic embryogenesis and cryopreservation protocols for A. pinsapo. Somatic embryogenesis was induced from mature zygotic embryos of A. pinsapo cultured on solid MS medium with macroelements at half-strength and supplemented with 20 g L-1 sucrose and 5 mg L-1 6-benzylaminopurine (BA). Embryogenic cultures successfully proliferated on solid medium with the same formulation supplemented with 20 g L-1 sucrose, 500 mg L-1 L-glutamine, 1 g L-1 casein hydrolysate and 1 mg L-1 BA. Different preconditioning and cryoprotective treatments were tested in order to optimize cryopreservation of embryogenic tissues by using the slow-cooling technique. Embryogenic cultures at their exponential growth phase, i.e. 12-14 days after the last subculture, were used as cryopreservation explants. The best results were achieved after sucrose preculture and cryoprotecion with PGD I (mixture of polyethylene glycol, glucose and DMSO I), with 100% of explants resuming somatic embryogenesis after thawing. Following fluorescein diacetate (FDA) staining, more intense and abundant green fluorescence could be observed in these samples, compared to those subjected to other preconditioning and cryoprotective treatments, thus evincing a higher proportion of viable cells after freezing in liquid nitrogen. Cold hardening did not improve cryotolerance. In fact, incubation at 5 °C for two weeks appeared to affect explants response, delaying tissue regrowth after cryopreservation. This is the first time in which somatic embryogenesis and cryopreservation have been reported in Spanish fir. The results obtained allow to establish the bases for the integration of these techniques into in situ and ex situ conservation strategies.